2022
DOI: 10.1136/bmjopen-2022-061962
|View full text |Cite
|
Sign up to set email alerts
|

Association between a History of herpes zoster and the risk of Sjögren’s syndrome: a nationwide, population-based, case–control study

Abstract: ObjectiveViral infection is an exogenous factor for Sjögren’s syndrome (SS). The relationship between herpes zoster infection and the ensuring risk of SS has remained unclear. This study investigated the association between a history of herpes zoster infection and the risk of SS through a nationwide population-based case–control study.DesignRetrospective case–control study.SettingGeneral population of Taiwan.Data source2003–2013 National Health Insurance Research Database of Taiwan.ParticipantsWe identified al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
(68 reference statements)
0
2
0
Order By: Relevance
“…A recent nation-wide, population-based, case–control study including 5751 SS patients and 28,755 matched controls showed a significant correlation between herpes zoster exposure and SS risk, which was greater when the interval between the last visit for herpes zoster infection and the index date was <3 months (OR adjusted for comorbidities = 3.13, 95%CI = 2.20–4.45) [ 234 ].…”
Section: Autoimmune Diseasesmentioning
confidence: 99%
“…A recent nation-wide, population-based, case–control study including 5751 SS patients and 28,755 matched controls showed a significant correlation between herpes zoster exposure and SS risk, which was greater when the interval between the last visit for herpes zoster infection and the index date was <3 months (OR adjusted for comorbidities = 3.13, 95%CI = 2.20–4.45) [ 234 ].…”
Section: Autoimmune Diseasesmentioning
confidence: 99%
“…16 More recently Huang et al suggested in a nationwide population based study, an association between recently raised antimuscarinic burden and acute cardiovascular events in older adults. 17 Consequently, whilst the use of antimuscarinic medication may not be contraindicated, it is important to be aware of comorbidities and the risk of polypharmacy resulting in an unacceptable anticholinergic load, particularly in the elderly. Alternatively, avoiding antimuscarinic therapy in those patients at a higher risk of cognitive decline may offer a rationale for improving drug adherence whilst maintaining efficacy and safety.…”
Section: Anticholinergic Burden-the Long Term Effects Of Antimuscarin...mentioning
confidence: 99%
“…Varicella is the main clinical feature after first infection with varicella zoster virus (VZV). The disease manifests as a painful vesicular rash and may present with herpes zoster (HZ) neuralgia due to occurrence of VZV from the latency of sensory root ganglia 1 . Systemic lupus erythematosus (SLE) is an autoimmune disease characterized by excessive activation of inflammatory immune cells and accumulation of a large number of proinflammatory cytokines.…”
Section: Introductionmentioning
confidence: 99%